Split liver transplantation: Report of right and left graft outcomes from a multicenter Argentinean group. Issue 1 (11th December 2015) - Halac, Esteban; Dip, Marcelo; Quiñonez, Emilio; Alvarez, Fernando; Espinoza, Johana Leiva; Romero, Pablo; Nievas, Franco; Maurette, Rafael; Luque, Carlos; Matus, Daniel; Surraco, Paz; Fauda, Martin; et al.
Abstract : Grafts from split livers (SLs) constitute an accepted approach to expand the donor pool. Over the last 5 years, most Argentinean centers have shown significant interest in increasing the use of this technique. The purpose of this article is to describe and analyze the outcomes of right‐side grafts (RSGs) and left‐side grafts (LSGs) from a multicenter study. The multicenter retrospective study included data from 111 recipients of SL grafts from between January 1, 2009 and December 31, 2013. Incidence of surgical complications, patient and graft survival, and factors that affected RSG and LSG survival were analyzed. Grafts types were 57 LSG and 54 RSG. Median follow‐up times for LSG and RSG were 46 and 42 months, respectively. The 36‐month patient and graft survivals for LSG were 83% and 79%, respectively, and for RSG were 78% and 69%, respectively. Retransplantation rates for LSG and RSG were 3.5% and 11%, respectively. Arterial complications were the most common cause of early retransplantation (less than 12 months). Cold ischemia time (CIT) longer than 10 hours and the use of high‐risk donors (age ≥ 40 years or body mass index ≥ 30 kg/m 2 or ≥ 5 days intensive care unit stay) were independent factors for diminished graft survival in RSG. None of the analyzed variables were associated with worse graft survival in LSG. Biliary complications were the most frequent complications in both groups (57% in LSG and 33% in RSG). Partial grafts obtained from liver splitting are an excellent option for patients in need of liver transplantation and have the potential to alleviate the organ shortage. Adequate donor selection and reducing CIT are crucial for optimizing results. Liver Transpl 22:63‐70, 2016 . © 2015 AASLD.